Oil shocks and the volatility of BRICS and G7 markets: SVAR analysis - Houda BenMabrouk; Wafa HadjMohamed (Cogent Economics & Finance, 2022)
Based on the Structural Vector Auto regression (SVAR) model, we study the impact of oil shocks on the volatility of the BRICS and G7 markets. We decompose oil shocks into three types: oil supply shocks, aggregate demand shocks and oil-specific demand shocks. The results indicate that there is a significant impact of oil shocks on both markets but this impact differs according to the nature of the shock and according to the studied market. We find that the reaction of all the considered market volatilities is more intensive for a demand shock especially for a specific demand shock than for a supply shock. BRICS and G7 markets volatilities react very similarly on impact to oil-specific demand shocks, while their responses present some differences to aggregate demand shocks and oil supply shocks. Our results reflect the changes experienced by the BRICS and G7 economies in recent years.
Keywords: G1; C58; Q41; 330; oil shocks; returns volatility; SVAR; BRICS; G7 countries